Psychometric validation of the Leadership Toolkit (2021) Emotional Intelligence Scale for teacher development in Chinese private universities - Sun, Qianqian; Abdullah, Mohd Khairuddin; Tan, ChoonKeong (Frontiers in Psychology, 2025)
Emotional intelligence (EI) is linked to effective teaching and educational leadership, yet few tools have been validated for Chinese private-university faculty. This study examined the psychometric properties of the Leadership Toolkit (2021) EI Scale in a sample of 450 teachers from Shandong province. Using stratified sampling, we administered a 37-item instrument covering five domains—self-awareness, managing emotions, motivating oneself, empathy, and social skills. Exploratory factor analysis supported a five-factor solution; confirmatory factor analysis indicated good fit (χ2/df, CFI, TLI, RMSEA, SRMR within commonly accepted thresholds). Convergent and discriminant validity were established (loadings ≥ 0.70; AVE ≥ 0.50; CR ≥ 0.70). Multi-group CFA demonstrated configural, metric, scalar, and residual invariance across gender, supporting unbiased cross-group comparisons. Internal consistency was high for the total scale and subscales. Findings suggest the instrument is reliable and culturally appropriate for assessing EI among Chinese private-university teachers, with implications for faculty development and leadership training. Future research should replicate with broader samples and examine links between EI and instructional outcomes. Despite these strengths, the study is limited by a single-province sample and self-report data, and it adopts a cross-sectional design.